Collaborative training in a virtual environment to increase productivity in a shipyard. (17th May 2019) - Dono, José Antonio Muiña; Rodríguez, Adolfo Lamas; Álvarez, David Chas
The paper addresses the potential of the combined use of simulation tools and game engine for an effective and efficient design to study complex problems. This study is focused on the shipbuilding problem, although the methodology and tools proposed can be extended to another application by other complex problems reaching the same satisfactory results. The innovative use of both tools has important advantages. From the training point of view, an economic saving, dynamism, customisation and motivation could be achieved, facilitating the implementation of a new work culture in the company. In addition, the realism of the simulation makes easier the extrapolation of knowledge to the reality and an estimation of the performance of the improvements. On the other hand, streamlining model development processes is possible using the users as testers and developers of the model, since the opinions of the users are relevant to the system design.